The Role of Sekar Gending "Kawitan" in Wayang Golek Purwa Performance - Maulana, Marsel Ridky; Gunawan, Iwan (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2024)
Gending "Kawitan" is a musical repertoire in the form of sekar- gending that must be presented in Wayang Golek Purwa performances. In its presentation, sekar-gending "Kawitan" has a very important role in the unity of Wayang Golek's performance as a whole. The purpose of writing this article is to reveal the role of sekar-gending "Kawitan" in Wayang Golek's performance based on its musical communication aspects. The method used is descriptive qualitative by conducting interviews with puppet artists and analyzing documents from several video recordings that have been broadcast online. Based on this method, the sekar-gending "Kawitan" has four parts: Kawitan Gancang, Kawitan Kendor, Bata Rubuh, and Gending Badaya. In terms of its role, gending "Kawitan" at least has a role as an instrumental music presentation, as a song presentation (vocals and instruments), as an illustration, and accompaniment for the puppeteer during Murwa, and as an accentuation in the ibing maktal scene. From the results of a section-by-section study, sekar-gending "Kawitan” has a tight structure and high musical communication complexity, due to the many interactions between musicians.